ANALISIS SENTIMEN PENGGEMAR SEPAK BOLA TERHADAP PROSES NATURALISASI PEMAIN TIMNAS INDONESIA PADA MEDIA SOSIAL X MENGGUNAKAN SUPPORT VECTOR MACHINE - Amal Anugra; Natalis Ransi; Gusti Arviana Rahman (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2025)
Abstract The naturalization process for players for the Indonesian national team has become a hot topic of discussion among football fans. Social media, especially platform X, has become one of the main places for fans to express their opinions and sentiments regarding this matter. This research aims to analyze football fans' sentiments towards the naturalization process of Indonesian national team players using the Support Vector Machine (SVM) method. Sentiment analysis can be used to analyze supporters' opinions and group them into three categories, namely positive, neutral and negative. This research uses the Support Vector Machine method to carry out classification which is carried out with a dividing line (hyperplane) that separates the classes in the data collection of supporters' tweets on social media X (twitter) who have opinions about naturalization. The research results show that the sentiment of Indonesian football fans towards the naturalization process for national team players mostly tends to be positive, with the proportion of positive sentiment reaching 38%, negative sentiment of 37%, and neutral sentiment of 25%. This analysis also reveals several factors that influence fan sentiment, including the performance of naturalized players on the field, football federation policies, and the influence of the media and public opinion.